PERAN GURU DALAM MENGHADAPI DISRUPSI TEKNOLOGI PENDIDIKAN BERBASIS AI - Rohmatul Nur Maghfiroh (Journal of Education and Learning, 2025)
The development of digital technology and artificial intelligence (AI) has created significant disruption in education, particularly to the traditional role of teachers as information centers and learning authorities. Teachers are now required to adapt to the shifting learning paradigm toward a learner-centered model and to utilize intelligent technology creatively and ethically. This study aims to describe the transformation of teachers' roles, analyze the challenges arising from AI-based technological disruption, and formulate professional adaptation strategies for teachers to maintain a balance between technology and human values. The research method used is library research with a qualitative-descriptive approach through the analysis of various scientific literature and educational policy documents for the 2020–2025 period. The results indicate that the transformation of teachers' roles includes functions as facilitators, mentors, digital learning designers, and AI pedagogical architects. Key challenges faced include technological competency gaps, resistance to change, and issues of ethics and data privacy. Adaptive strategies include improving digital literacy, developing blended and personalized learning models, and strengthening the humanistic dimension and character of students. Teachers remain central to ensuring that AI becomes a means to humanize the learning process, not replace it.